A comparison of waiting times for assessment and epilepsy surgery between a Canadian and a Mexican referral center. Issue 4 (19th October 2017) - Martínez‐Juárez, Iris E.; Funes, Bianca; Moreno‐Castellanos, Julio C.; Bribiesca‐Contreras, Elisa; Martínez‐Bustos, Verónica; Zertuche‐Ortuño, Lizeth; Hernández‐Vanegas, Laura E.; Ronquillo, Lizbeth Hernandez; Rizvi, Syed; Adam, Wu; Tellez‐Zenteno, Jose F.
Summary: Objective: To provide a comprehensive transnational overview of wait times for epilepsy surgery in Canada and Mexico. Methods: We reviewed all cases referred for epilepsy surgery between 2007 and 2015 at the Saskatchewan Epilepsy Program Royal University Hospital (SEP) (n = 70; Saskatoon, Canada) and the National Institute of Neurology and Neurosurgery (NINN) (n = 76; Mexico City, Mexico) and compared wait times, calculated as the time from diagnosis of epilepsy on assessment at an epilepsy center to epilepsy surgery. Results: Mean wait times were similar across centers. Mean patient age was 37.4 ± 9 years (NINN) and 36.7 ± 13.2 years (SEP). The mean time from epilepsy diagnosis to referral was 18.9 (NINN) and 16.9 years (SEP), p = 0.30; first consult with the epileptologist, 19.7 (NINN) and 17.4 years (p = 0.23); neuropsychology consult, 21.4 (NINN) and 17.9 years (SEP); video electroencephalogram (video‐EEG) telemetry, 21.1 (NINN) and 18.6 months (SEP); initial neurosurgical consult, 21.9 (NINN) and 19.1 years (SEP) (p = 0.35); and epilepsy surgery, 19.7 (NINN) and 19.6 years (SEP) (p = 0.29). Significance: This is the first study to compare wait times between Canada and Mexico. Despite disparity in their health delivery systems and financial resources, surgical wait times appeared to be protracted in both nations, confirming that delayed treatment is a universal problem that requires collaborative scrutiny.